Mechanisms for the inhibition of amyloid aggregation by small ligands. Issue 5 (29th September 2016) - Ramazzotti, Matteo; Melani, Fabrizio; Marchi, Laura; Mulinacci, Nadia; Gestri, Stefano; Tiribilli, Bruno; Degl'Innocenti, Donatella
Abstract : This work investigates by biochemical, biophysical and MD techniques the opposite anti-amyloid properties of resveratrol and rosmarinic acid on the aggregation of hen egg white lysozyme (HEWL). Differences in association energy and contact maps were found that explain the different behaviours. Abstract : The formation of amyloid aggregates is the hallmark of systemic and neurodegenerative disorders, also known as amyloidoses. Many proteins have been found to aggregate into amyloid-like fibrils and this process is recognized as a general tendency of polypeptides. Lysozyme, an antibacterial protein, is a well-studied model since it is associated in human with systemic amyloidosis and that is widely available from chicken eggs (HEWL, hen egg white lysozyme). In the present study we investigated the mechanism of interaction of aggregating HEWL with rosmarinic acid and resveratrol, that we verified to be effective and ineffective, respectively, in inhibiting aggregate formation. We used a multidisciplinary strategy to characterize such effects, combining biochemical and biophysical methods with molecular dynamics (MD) simulations on the HEWL peptide 49–64 to gain insights into the mechanisms and energy variations associated to amyloid formation and inhibition. MD revealed that neither resveratrol nor rosmarinic acid were able to compete with the initial formation of the β-sheet structure. We then tested the association of two β-sheets, representing the model of an amyloid core structure. MD showed that rosmarinic acid displayed an interaction energy and a contact map comparable to that of sheet pairings. On the contrary, resveratrol association energy was found to be much lower and its contact map largely different than that of sheet pairings. The overall characterization elucidated a possible mechanism explaining why, in this model, resveratrol is inactive in blocking fibril formation, whereas rosmarinic acid is instead a powerful inhibitor.